The Role of Islamic Banking in Preventing and Overcoming Online Gambling through the Application of Sharia Principles - Fitriyanti, Fadia; Putri, Syahmilian (Widya Yuridika, 2024)
Online gambling has become a significant social concern, particularly among Muslim communities. The allure of quick riches and the ease of accessibility through the internet have contributed to the rise of online gambling addiction. Islamic banking, with its adherence to Sharia principles, offers a unique perspective on addressing this issue. This paper explores the potential role of Islamic banking in preventing and overcoming online gambling through the application of Sharia principles. The main objective of this paper is to examine how Islamic banking can contribute to curbing online gambling by promoting financial literacy, fostering responsible financial behavior, and providing alternative investment options aligned with Sharia principles. The paper also aims to identify specific Sharia-compliant financial products and services that can be employed to reduce the appeal of online gambling and encourage individuals to seek more ethical and sustainable forms of wealth creation. This paper demonstrates that Islamic banking, guided by Sharia principles, holds immense potential to address the growing concern of online gambling among Muslim communities. By implementing tailored financial solutions and fostering a culture of financial responsibility, Islamic banking can contribute to a healthier and more ethical financial landscape for all.